Cosmetic surgeries regulations: a comparative legal study between Malaysia, Canada and China / Nur Atiqah Hamran, Umi Kalsum Mat Zuhri and Nur Aminatul Zahriah Khairolanwar - Hamran, Nur Atiqah; Mat Zuhri, Umi Kalsum; Khairolanwar, Nur Aminatul Zahriah (2014)
In the field of cosmetic surgery in Malaysia, legislation needs to be enacted as soon as possible to govern the fast growing industry. This is due to the fact that, the lack of such laws has triggered the blooming of illegal surgeons and beauty salons. In view of an increase in botched surgeries, stern actions need to be taken by the authorities against doctors who performed such procedures despite not being qualified. The current guidelines on aesthetic medicine need to be legislated into law so that it can be legally enforced and regulated. Presently the Health Ministry applies the Private Healthcare Facilities and Services Act (PHFSA) 1998 and the Medical Act 1971 if untrained and unqualified doctors conduct cosmetic surgeries. However, by looking at the increasing cases that involved botched surgery, it seems like the law is not sufficient.